Discoloration difference between acrylic artificial teeth exposed to filter- and electronic-cigarette smoke in the Laboratory Faculty of Dentistry, Muslim University of Indonesia in 2017 - Chusnul Chotimah; Mohammad A. Ramadan (Journal of Dentomaxillofacial Science, 2020)
Objective: To determine of artificial teeth color discoloration different between exposure of cigarette’s and electric cigarette’s smoke in the Laboratorium FKG UMI 2017. The simulator of smoking, artificial teeth, cigarette’s, CIE Lab.Material and Methods: Acrylic is most commonly used material for articial teeth. Acrylic is easily stained by food, beverage, chemical, and smoking habit. Cigarette and electric cigarette are commonly consumed by most people. Cigarette contains brownish substance called tar meanwhile electric cigarette contains of many chemical substances.Results: Data were recorded after exposure of cirarettes’s and analyzed by statistic test used Independent sampe T test whit the significance level ? = 0.05. Cigarette smoke affects the color of acrylic artificial teeth. Meanwhile, electric cigarette effect the color of acrylic teeth but insignificantly. There are artifisial teeth color discoloration different between exposure of cigarette’s and electric cigarette’s smoke with p=0.010 < ?=0.05.Conclusion: This study shows that there is a discoloration difference between acrylic artificial teeth exposed to filter- and electronic-cigarette smoke